Penggunaan Beauty Key Opinion Leader Dalam Strategi Membangun Kesadaran Merek Produk Kecantikan Lokal Indonesia - Paramasari, Silvia Nevane (Kinesik, 2024)
Key Opinion Leader s are individuals who have great influence in a particular industry or community, especially in the context of marketing and promotions. The aim of this research is to analyze marketing communication strategies in building brand awareness of local Indonesian beauty products. The method used is qualitative descriptive research with an interactive analysis technique approach in analyzing data. Data collection was carried out by interviews, observations and documentation studies. The research results show that the marketing communication strategy combines several existing strategies, namely KOL selection strategy, creative content creation, unboxing content with PR packages, and hard selling content.